Keberkesanan kerja berpasukan yang diamalkan oleh staf-staf unit sumber manusia dan kualiti, Jabatan Ketua Menteri - Rajes, Bin Pisoon. (Universiti Malaysia Sarawak (UNIMAS), 2003)
The purpose ofdoing this research is to know the effectiveness ofteamwork that have done by staffat Human Resource an Quality Unit, Chief Minister Department according to the related factor. The related factor in this research is communication, leadership, commitment and working together. These factors are dependent variable for the effectiveness of teamwork. Sample of research is consisted of40 employees. It is found out that the majority ofrespondent is from the human resource alld entrepreneur development department. The determination ofdescriptive analysis also shows that majority respondent services more than one year. According to analysis it is found the result ofevery factor are average. The hypothesis was exam with the correlation Pearson. The result found that every factor have significant with the effectiveness of teamwork. It is also found that working together is the dominant factor for effective teamwork. The finding also found some suggestion to orgallization andfuture researcher.